Numerical studies of urban heat island in greater Kuala Lumpur, Malaysia : from surface and boundary layer conditions to local air pollution - Ooi, Chel Gee (2017)
Rapid urbanization of cities has greatly modified the thermal and dynamic profile in the urban boundary layer. This thesis attempts to study the effect of urban heating on the local climate and air quality for a tropical coastal urban agglomeration, Greater Kuala Lumpur (GKL) in Malaysia. A state-of-art numerical model, Weather Research and Forecast Model (WRF) is used to identify the influence of urbanization through modification of urban surfaces. In order to thoroughly study the environmental impact of land use change in GKL, this thesis begins with the local urban heating on the surface layer before extending to the influence on the boundary layer circulation and its atmospheric composition.